Integration of Refugees: Lessons from Bosnians in Five EU Countries - Mikkel Barslund; Matthias Busse; Karolien Lenaerts; Lars Ludolph; Vilde Renman (Intereconomics, 2017)
In this study, we reviewed the integration experience of Bosnian refugees displaced during the Bosnian war in the early 1990s. We compare reception conditions among the five Western European countries that played host to the majority of refugees at the time and track their labour market experience as well as, to the extent possible, education outcomes of second generation Bosnians.
Keywords: 330